Multi-Year Assessment of Phenotypic Variability and Stability in 49 Peruvian Grapevine (Vitis spp.) Accessions Using AMMI, GGE, and WAASBY Models - Ccapa Ramírez, Karina Beatriz; Tarazona Ramírez, Cesar Mario; Carrillo Zavala, Pedro Víctor; Cueva Carhuatanta, César Aldair; Aybar Peve, Leandro Joel; Saenz Rodriguez, Hanz; Hermoza Gutiérrez, Marián Alicia; Cántaro Segura, Hector Baroni; Fernandez Huaytalla, Elizabeth; Gutiérrez Reynoso, Dina Lida; Quispe Jacobo, Fredy Enrique (MDPI, 2026)
Grapevines face the dual challenge of sustaining yield and fruit quality under arid and increasingly variable environmental conditions. This study characterized the phenotypic variability and multi-year stability of 49 grapevine (Vitis spp.) accessions conserved in the Chincha germplasm bank over three consecutive growing seasons, with the aim of identifying promising material for table grape, pisco (a traditional grape-based distille spirit from Peru), and wine production. Morphological traits (cluster weight, berry weight and dimensions), colorimetric parameters (CIELAB), and physicochemical attributes (moisture, dry matter, soluble solids, pH, titratable acidity, maturity index, and reducing sugars) were evaluated. Multivariate analyses (PCA, hierarchical clustering), genotype × environment interaction models (AMMI and GGE), stability indices (ASV and WAASBY), and assessments of interannual stability were applied, together with a multi-criteria selection index tailored to the intended end use. The results revealed two contrasting phenotypic profiles: one characterized by high berry volume/weight and elevated water content and another with smaller berries but higher dry matter, sugars, balanced acidity, and superior maturity indices. Genotypic effects were predominant for size-related traits such as berry weight, whereas titratable acidity and reducing sugars exhibited a more pronounced genotype × year interaction, supporting the use of AMMI models and the WAASBY index to select genotypes that are both productive and stable. The ranking identified accessions PER1002061, PER1002062, and PER1002168 as outstanding candidates for table grape production; PER1002076, PER1002097, and PER1002156 for pisco; and PER1002122, PER1002131, PER1002135, and PER1002098 as accessions with high oenological potential. Overall, these findings highlight the value and diversity of Peruvian grapevine germplasm and provide a foundation for breeding programs targeting varieties adapted to specific market niches, including table grape, wine, and pisco.